2016
DOI: 10.1097/01.prs.0000479982.67922.8a
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Plastic Surgery Resident Education

Abstract: The challenge of the current graduate medical education environment requires in plastic surgery acceptance of those contemporary pressures that cannot be substantially modified and address of those that can be successfully met. To do so implies an examination of conference didactics, intraoperative teaching, and a valid assessment of resident performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…2931 Furthermore, the ability to accurately document and thoroughly discuss complications is a critical skill all residents must develop to be prepared for independent practice. 9,12,32,33 Prior studies have demonstrated patients are often unsatisfied with physicians’ disclosure of complications and medical errors, with lack of information, emotional support, and thoroughness of discussion being the most prevalent reasons cited. 34,35 Poor communication about complications can deteriorate the physician-patient relationship and is associated with a significantly greater likelihood of malpractice lawsuits when compared to open and thorough discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2931 Furthermore, the ability to accurately document and thoroughly discuss complications is a critical skill all residents must develop to be prepared for independent practice. 9,12,32,33 Prior studies have demonstrated patients are often unsatisfied with physicians’ disclosure of complications and medical errors, with lack of information, emotional support, and thoroughness of discussion being the most prevalent reasons cited. 34,35 Poor communication about complications can deteriorate the physician-patient relationship and is associated with a significantly greater likelihood of malpractice lawsuits when compared to open and thorough discussion.…”
Section: Discussionmentioning
confidence: 99%
“…While M&M conferences have a valuable role in surgical education, these conferences are only beneficial if they accurately reflect the complications occurring over the defined time period. 11,12 Unfortunately, current methods for capturing a comprehensive profile of complications for analysis at M&M conference are often inadequate. 1315 The most common of these methods include the chief resident on service reporting all complications at set time points or all residents on service maintaining their own list of complications, which are subsequently collated prior to M&M conference.…”
Section: Introductionmentioning
confidence: 99%
“…In North America, plastic surgery trainees routinely gathered a few times during a week with their faculty for didactic sessions and supplemented their knowledge with online modules. 4 In addition, large residency programs allowed their trainees to be exposed to different fields of plastic surgery, but for smaller programs, there was a limit of exposure. The learning experience for trainees was even narrower in developing countries, especially those with limited resources to perform variety of surgeries and established education infrastructures.…”
Section: Sirmentioning
confidence: 99%
“…◦ Innovate simulation tools for resident acquisition of technical skills and use of contemporary technology for instruments of objective assessment of technical proficiency and nontechnical aptitudes. 7 …”
Section: The Future Of Plastic Surgery Education Is Digitalmentioning
confidence: 99%